2013
DOI: 10.2215/cjn.06470612
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Ambulatory BP Monitoring among Patients with CKD

Abstract: . Data from 1075 patients (682 men) were analyzed to determine BP control and factors associated with the ABPM parameters.Results The prevalence of masked hypertension was 30.9%, whereas that of white-coat hypertension was 5.6%. With advancing CKD stage, the percentage of persistent hypertension increased from 21.7% to 36.1%. Diabetes, antihypertensive medicine use, and low estimated GFR (eGFR) were significantly associated with the difference between office BP and ambulatory BP (1.7 mmHg, 2.6 mmHg, and 0.6 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
52
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 44 publications
(32 reference statements)
9
52
2
1
Order By: Relevance
“…The prevalence of masked hypertension was similar in CRIC participants when compared with other cohorts of patients with CKD, such as in the African American Study of Kidney Disease and Hypertension Cohort Study and the CKD Japan Cohort, at 43% and 31% respectively (9,(27)(28)(29). However, in a meta-analysis by Agarwal et al and a crosssectional study from Spain, masked hypertension was present in less than 10% of CKD patients (30,31).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The prevalence of masked hypertension was similar in CRIC participants when compared with other cohorts of patients with CKD, such as in the African American Study of Kidney Disease and Hypertension Cohort Study and the CKD Japan Cohort, at 43% and 31% respectively (9,(27)(28)(29). However, in a meta-analysis by Agarwal et al and a crosssectional study from Spain, masked hypertension was present in less than 10% of CKD patients (30,31).…”
Section: Discussionmentioning
confidence: 63%
“…Earlier studies of CKD cohorts have shown an increased risk for masked and sustained hypertension with elevated urine protein, but analyses were unadjusted or obtained from small cohorts (9,27,33). In CRIC, masked hypertension was associated with low eGFR, and masked and sustained hypertension were associated with elevated urine protein, independent of other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…How reliable is office assessed blood pressure in chronic kidney disease (CKD) patients and kidney transplant (KTx) recipients is yet to be determined, as it was shown before that office BP tends to overestimate blood pressure control in renal transplantation [3]. On the other hand, ambulatory blood pressure monitoring (ABPM) seems to offer a more reliable view over arterial hypertension both in CKD and KTx patients [4][5] and also a prognostic superiority [6]. Due to the pro-hypertensive potential of immunosuppressive drugs [7][8], blood pressure control is one of the major targets for outcome management in KTx patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, data consistently show that the lack of recognition of high BP outside the clinic-masked hypertension-is associated with increased cardiovascular damage 8,12 and cardiovascular morbidity and mortality. 9,[13][14][15][16][17][18] Although emerging data in CKD also support this concept, [19][20][21][22][23][24][25][26][27][28] whether patients with CKD also have a high prevalence of MHTN, and if so what the determinants of this condition are, and how reproducible this diagnosis is, remains to be demonstrated prospectively in studies dedicated to this purpose. Furthermore, the ability of home BP to diagnose MHTN and its reproducibility remains scarcely studied even in the general population.…”
mentioning
confidence: 99%